Optimization of Fermentation Conditions for Red Pigment Production from Phoma herbarum (FGCC#54) under Submerged Cultivation - Singh2, Sadaf Quereshi1*, A.K. Pandey2; Jaya (Journal of Phytology, 2010)
An extracellular pigment-producing coelomycetous phytopathogenic fungi belonging to the genus Phoma was isolated from phyllosphere of Parthenium hysterophorus L. The cell free culture filtrate contained the red pigment. The optimal culture conditions for red pigment production were as follows: Sucrose (742 units), Potassium Nitrate (784 units), pH (736 units), temperature (749 units).